A feasibility study in establishing Doux Delicieux Pasalubong Especial - Mason, Jeremie M., author; Calle, Angelita A., author; Soriano, Merilyn D., author; Nepomuceno, Lucena C., adviser (Rosario, Cavite : Cavite State University-CCAT Campus, 2002)
Thesis Abstract
A feasibility study in establishing--Cavite State University-CCAT Campus, 2002.
Includes bibliographical references and appendices.
In English text.
Keywords: Pastries; Pies; Baked products; Filipino native delicacies; Feasibility study; Affordable prices; Homemade taste